Appropriation of Digital Machines and Appropriation of Fixed Capital as the Real Appropriation of Social Being: A Comment on Toni Negri’s Article “The Appropriation of Fixed Capital: A Metaphor?” - Christian Fuchs (tripleC: Communication, Capitalism & Critique)
This article is a reflection and comment on Toni Negri’s essay “The Appropriation of Fixed Capital: A Metaphor?”. The comment first points out aspects of Negri’s reception of Marx. It stresses the continuities of the Grundrisse and Capital. In both, we can find a dialectical concept of technology. Second, this paper points out that Negri’s notion of the appropriation of technology/fixed capital should best be read as a critique of techno-optimism à la Marshall McLuhan and of techno-pessimism à la Martin Heidegger. Negri advances a dialectical concept of appropriation that is focused on the appropriation, and therefore transformation, of technology and society. Third, this reflection asks: What does it mean to appropriate digital machines? Concrete strategies of digital appropriation are outlined. The author argues that commons-public partnerships can be powerful political means of struggle against digital capitalism.